Acute heart failure due to autoimmune myocarditis under pembrolizumab treatment for metastatic melanoma. Issue 1 (21st April 2015) - Läubli, Heinz; Balmelli, Cathrin; Bossard, Matthias; Pfister, Otmar; Glatz, Kathrin; Zippelius, Alfred
Abstract : Antibodies that stimulate the immune system by targeting inhibitory T cell receptors were successfully introduced into oncological practice and are capable to overcome tumor-induced immune evasion. In particular, targeting of the inhibitory receptors CTLA-4 and PD-1 or its ligand PD-L1 have been shown to be beneficial for patients with melanoma, renal cell cancer, non-small cell lung cancer and a growing list of other cancers with impressive response rates. Here, we report a severe, potentially life-threatening side effect of anti-PD-1 immunotherapy with pembrolizumab, which has not been previously described in the literature. A 73-year-old woman with metastatic uveal melanoma treated with pembrolizumab in third line developed severe heart failure due to pembrolizumab-mediated autoimmune myocarditis. Echocardiographic studies revealed a severely impaired left ventricular function with dyssynchrony. All tests for cardiotropic viruses were negative and histological analysis of a myocardial biopsy showed lymphocytic infiltration with a predominance of CD8 positive cells and a reduction of FOXP3 positive regulatory T cells. After initiation of corticosteroids and guideline-conform heart failure therapy, the symptoms rapidly improved and the left ventricular function recovered. While autoimmune myocarditis is a documented side effect of other checkpoint inhibitors, as for example ipilimumab and in one case with anti-PD-L1 antibody, it is not described for anti-PD-1-antibodies like pembrolizumab or nivolumab. As the FDA recently approved both pembrolizumab and nivolumab for melanoma progressing after anti-CTLA-4 treatment with ipilimumab, more patients will soon receive anti-PD-1 therapy. Thus, it is important to be aware of such rare, but severe immune-related adverse events.